The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1016/s0002-9440(10)62265-1
|View full text |Cite
|
Sign up to set email alerts
|

Capsule Structure Changes Associated with Cryptococcus neoformans Crossing of the Blood-Brain Barrier

Abstract: Cryptococcus neoformans is a yeast responsible for disseminated meningoencephalitis in patients with cellular immune defects. The major virulence factor is the polysaccharide capsule. We took advantage of a relevant murine model of disseminated meningoencephalitis to study the early events associated with blood-brain barrier (BBB) crossing. Mice were sacrificed at 1, 6, 24, and 48 hours post-intravenous inoculation, and classical histology, electron microscopy, and double immunofluorescence were used to study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
190
0
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 185 publications
(203 citation statements)
references
References 64 publications
11
190
0
2
Order By: Relevance
“…Previous studies have suggested that strains of C. neoformans that express larger polysaccharide capsules may have difficulty transversing the blood-brain barrier and establishing infection in the central nervous system (8,24). Perhaps by expressing a larger polysaccharide capsule to avoid the internalization by activated macrophages, the ⌬isc1 strain is hindering its own ability to disseminate to the brain in an immunocompetent host, such as the CBA/J mouse.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have suggested that strains of C. neoformans that express larger polysaccharide capsules may have difficulty transversing the blood-brain barrier and establishing infection in the central nervous system (8,24). Perhaps by expressing a larger polysaccharide capsule to avoid the internalization by activated macrophages, the ⌬isc1 strain is hindering its own ability to disseminate to the brain in an immunocompetent host, such as the CBA/J mouse.…”
Section: Resultsmentioning
confidence: 99%
“…C. neoformans is an extremely adaptable environmental yeast that can withstand a variety of harsh conditions (63)(64)(65) and is capable of living in close association with numerous organisms, including plants (66,67), birds (68,69), predatory amoebae (70), and mammals (71,72), notably humans (73,74). The cryptococcal capsule in particular is a dynamic structure whose morphology and architecture change with growth conditions (75)(76)(77) and the local environment (52,55). It may be that specific capsular features are only required in a subset of the diverse ecological niches inhabited by this yeast.…”
Section: Discussionmentioning
confidence: 99%
“…Estudos realizados em casos de criptococose humana e infecções experimentais em animais têm também demonstrado variações na espessura da cápsula, na parede e no diâmetro da célula das leveduras de acordo com o órgão analisado e o tempo de infecção (Feldmesser et al 2001, Del Poeta 2004, Charlier et al 2005, Xie et al 2012. Diversos autores têm sugerido que o espessamento da cápsula ocorre principalmente em leveduras maduras devido à adição de novos polissacarídeos e nanoproteínas à estrutura pré-existente (Charlier et al 2005, McFadden et al 2006. Apesar de haver variação na espessura da cápsula das leveduras nos casos de criptococose deste estudo, não foram observadas leveduras totalmente sem cápsula.…”
Section: Quadro 2 Localização E Macroscopia Das Lesões Em Casos De Cunclassified